Correlational Analysis of ALS Progression and Serum NfL Measured by Simoa Assay in Chinese Patients - Sugimoto, Kazuo; Han, Yi; Song, Yuebo; Gao, Ying (Frontiers in Neurology, 2020)
Abstract Background: Neuroﬁlament light chain (NFL) was believed to be a promising biomarker for the diagnosis of Amyotrophic lateral sclerosis (ALS) and disease burden evaluation. Objective: To determine the serum NFL level and its clinical relevance, including its association with disease severity (evaluated by the ALS Functional Rating Scale–revised (ALSFRS-r) score and King’s College staging system) and progression (evaluated by the disease progression rate (DPR) and diagnostic delay), in ALS patients in China. Method: Serum NFL levels were detected using the Single Molecule Array (Simoa) technology in 30 ALS patients and 20 healthy controls (HCs). Results: There was a significant elevated levels of serum NFL in patients with ALS than in the HCs (P < 0.001). The serum NFL levels were signiﬁcantly higher in rapidly progressive ALS and patients in Stage 3 than in slowly progressive ALS and patients in Stage 2. (PDPR < 0.001, PDiagnostic delay = 0.019; Pstage = 0.033). Furthermore, the serum NFL levels negatively correlated with the diagnostic delay (R2 = 0.23, P = 0.016), the ALSFRS-r score (R2 = 0.15, P = 0.047) and disease duration (R2 = 0.15, P = 0.034), and positively correlated with the DPR (R2 = 0.42, P < 0.001). Conclusions: The present study preliminarily investigated the diagnostic value of serum NFL and its clinical relevance in the Chinese ALS population using the ultrasensitive Simoa technology. The results demonstrated that the level of serum NFL may become a potential biomarker for ALS diagnosis and indicate disease severity and progression.